Humaneness and creativity in the moral development of young people - Natal'ya G. Bryukhova; Svetlana V. Agafonova (Rossijskij psihologičeskij žurnal., 2017)
Humaneness is a manifestation of morals. The present paper discusses the problem of overcoming moral crisis in modern society and analyses the development of humaneness and creativity in the moral development of young people. Features of self-actualizing personality in foreign humanistic psychology do not correspond to the concept of moral personality in domestic psychology. The analysis demonstrated differences in approaches to the concepts of “humaneness” and “creativity”. The empirical study carried out in 2012–2016 involved 992 persons. The obtained results revealed average levels of young people’s humaneness and creativity. Moreover, psychology and pedagogy students and young experts (especially girls) had lower rates of “good” and “evil” functions than respondents in other samples. Hence, moral development and a moral choice between good and evil are especially important in the formation of professionally significant qualities of future pedagogues and psychologists. The data showed (a) the negative correlation among creativity, “good”, and “humaneness factor”, (b) the positive correlation between creativity and “evil”. The development of young people’s creativity decreases the level of moral development by the factor of humaneness. The theoretical analysis and the findings from the empirical study of the association between humaneness and creativity established the necessity of critical understanding of foreign humanistic psychological propositions, because of their contradiction with the person’s realization of enduring universal moral principles and norms. The formation of the ability to assess what is going on according to the criteria of humaneness is required to support the personal development of young people.